Mediated nostalgia : individual memory and contemporary mass media - Lizardi, Ryan, 1981- (Lexington Books, 2014)
Mediated Nostalgia works to help understand the cultural, historical, and sociological implications of a past-obsessed media industry. It takes a cross-media and interdisciplinary approach in its study of the nostalgia common in contemporary digital media, film, television, and video games.